2021
DOI: 10.31254/phyto.2021.10105
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Combo Therapy’ for Oestrus Induction in Postpartum Anoestrus Cows

Abstract: The research was aimed at studying the effect of a ‘Herbal combo therapy’ (HCT) on induction of oestrus and enhancement of fertility in postpartum anoestrus (PPA) in crossbred cows. Crossbred cows (n = 24) which were diagnosed for true anoestrus condition were utilized for the study. All the cows were dewormed and randomly divided into two groups (i) Control group (n = 10): No treatment schedule and (ii) Treatment group (n = 14): HCT involving a sequential administration of Raphanus sativus, Aloe vera, Moringa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…(2021) [11] reported an overall conception rate of 57.1% among the post-partum anoestus cows (n=14) treated with the similar EVM preparations mentioned in the current study. Aloevera (A. vera) and white radish (R. sativus) are reported to have anti-microbial and anti-inflammatory effacts (Surjushe et al, 2008, Bettaieb et al, 2011) [1] .…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…(2021) [11] reported an overall conception rate of 57.1% among the post-partum anoestus cows (n=14) treated with the similar EVM preparations mentioned in the current study. Aloevera (A. vera) and white radish (R. sativus) are reported to have anti-microbial and anti-inflammatory effacts (Surjushe et al, 2008, Bettaieb et al, 2011) [1] .…”
Section: Methodssupporting
confidence: 56%
“…Dutta et al (2020) had recorded high efficacy of EVM for the management of diarrhoea, pyrexia and mastitis in cattle. Satheshkumar et al, (2021) [11] also reported encouraging results with herbal combinations on induction of oestrus and enhancement of fertility in crossbred cows with postpartum anoestrus. The work reported here was undertaken to study the field efficacy of "Combination of Herbs" in bovines with the history of repeat breeding in the Kolhapur district, Maharashtra, India.…”
Section: Introductionmentioning
confidence: 98%
“…Likewise, Prasad et al (2020) buffaloes consuming green grass along with curry leaves and moringa leaves were higher when compared to the ones fed untreated rations. Similar results were observed by Kumar et al (2021) in lactating cows and Dutta et al (2022) in cattle and buffaloes fed diet incorporated with moringa leaves.…”
Section: Sex Hormonal Parameterssupporting
confidence: 84%
“…This plant has anti-inflammatory, immunestimulating, and antibacterial properties to make it beneficial (Satheshkumar et al, 2021)…”
Section: Aloe Barbadensis Andmentioning
confidence: 99%